The Effect of Sky View Factor on Air temperature in High-rise Urban Residential Environments - Golnar Baghaeipoor; Nazanin Nasrollahi (Journal of Daylighting, 2019)
Urban geometry is defined by the height, length, width, and distance of buildings, which affect the urban environment and its microclimate, especially a high-rise and high-density urban environment, such as Tehran. In this regard, the Sky View Factor (SVF) may often be a desirable criterion in identifying the interaction between urban geometry and the air temperature in densely populated areas. The research aim was to investigate the SVF in an urban microclimate of a high-rise residential complex and to evaluate its effect on air temperature. To do so, a case study of the Atisaz in Tehran as a high-rise urban residential complex was selected as the fundamental study model of this research. The selected configuration was simulated and analyzed using the ENVI-met model. In addition, the effects of the SVF value on air temperature are discussed throughout this paper. SPSS software was used to correlate, analyze, and construct an accurate relationship between air temperature and SVF during the hottest and coldest days of the year. The obtained results showed that there is a direct relation between SVF and air temperature during the day as well as an inverse relation at night. Furthermore, there was a small difference in air temperature for dense and semi-dense spaces in the high-rise residential complex.